2022
DOI: 10.3390/ijerph19052706
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diet Consistency on the Mandibular Morphology: A Systematic Review of Studies on Rat Models

Abstract: Apart from genetics, environmental factors, such as food consistency, may affect craniofacial morphology and development. The present systematic review aims to systematically investigate and appraise the available evidence regarding the effect of diet consistency on the anatomical structures of the basal bone of the rat mandible. The search was performed without restrictions in five databases (PubMed, Scopus, Web of Science, ProQuest Dissertations and Theses Global, including grey literature) and hand searchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…In our study twenty-four wistar rats were grouped into hard diet group and soft diet group. Wistar rats were the experimental animal of choice because they are small, easy to house, report a minimal social concern, are short-lived and have well-known genetics, closely related to human development [ 12 , 13 , 14 , 15 , 16 ]. We included only female rats in our study in order to minimize any possible bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study twenty-four wistar rats were grouped into hard diet group and soft diet group. Wistar rats were the experimental animal of choice because they are small, easy to house, report a minimal social concern, are short-lived and have well-known genetics, closely related to human development [ 12 , 13 , 14 , 15 , 16 ]. We included only female rats in our study in order to minimize any possible bias.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the impact of diet consistency on craniofacial growth triggers lots of research. Various experimental studies, mainly in wistar rats, studied the effect of diet consistency to craniofacial growth [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. During the last century, the human masticatory muscles demands seem to be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research protocols looked over the effect of diet consistency to growth by using rats as experimental animals. Rats are usually the experimental animals of choice because they are small, can be easily housed, report a minimal social concern, have a short lifespan, and their genetic background and growth is well known, resembling those of humans [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the introduction of different food textures has a positive impact on the maturation of chewing and influences the preferences and future eating habits (Kostecka et al, 2020; Linas et al, 2020). Indeed, a recent study showed that food consistency may affect the morphology of anatomical structures and the overall growth of rat mandibles (Karamani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%